2005
DOI: 10.1038/sj.bjc.6602853
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HER-2 DNA vaccine protects Syrian hamsters against squamous cell carcinomas

Abstract: This paper illustrates the efficacy of DNA vaccination through electroporation in the prevention of oral transplantable carcinoma in Syrian hamsters. At 21 and 7 days before tumour challenge, 19 hamsters were vaccinated with plasmids coding for the extracellular and transmembrane domains of rat HER-2 receptor (EC-TM plasmids), whereas 19 control hamsters were injected intramuscularly with the empty plasmid. Immediately following plasmid injection, hamsters of both groups received two square-wave 25 ms, 375 V c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The collaboration of antibody-and cellmediated cytotoxic responses in protection against ERBB2 þ tumors has been clearly documented (27). We have previously shown that electroporation of the EC-TM plasmid in hamsters elicits a protective anti-ERBB2 antibody-and cell-mediated cytotoxic response against ERBB2 þ transplantable tumors (21). In the present study, a similar cytotoxic response was also elicited in the few ERBB2 vaccinated hamsters tested (data not shown).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The collaboration of antibody-and cellmediated cytotoxic responses in protection against ERBB2 þ tumors has been clearly documented (27). We have previously shown that electroporation of the EC-TM plasmid in hamsters elicits a protective anti-ERBB2 antibody-and cell-mediated cytotoxic response against ERBB2 þ transplantable tumors (21). In the present study, a similar cytotoxic response was also elicited in the few ERBB2 vaccinated hamsters tested (data not shown).…”
Section: Discussionsupporting
confidence: 69%
“…However, it is a self-tolerated molecule and triggering a response against it has to circumvent central and peripheral tolerance (4,15). Data in mice (24) and hamsters (21) have shown that EC-TM plasmid electroporation is an effective way to break tolerance. However, the antibody response thus induced is short lived and frequent electroporations are required for a sustained control of carcinogenesis (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in one study in hamsters, the HER2 receptor was expressed in skin via electroporation and subsequently, the animals were challenged with HER2 positive carcinogen-induced oral carcinoma cells. Thirty-seven percent of animals that received the HER2 gene developed neoplasia compared to 74% of control animals (Berta et al, 2005). …”
Section: Electroporation Of Skin: Vaccination Wound Healing and mentioning
confidence: 99%